The Role of Trust as an Informal Mechanism in the Management Control System of Performance Effectiveness - Fachmi Pachlevi Yandra (Universitas Hayam Wuruk Perbanas, 2017)
Performance is a variable explaining the effectiveness of internal control systems that managed based on management accounting information and functions. There are some aspects of behavior that remain unexplained in understanding the effectiveness of the performance of organizations and individuals affected by the data and accounting functions. In addition, social mechanisms such as culture, honesty, group identification and trust play an important role in mitigating agency problems. This study aims to investigate what and how the role of trust in organizational performance is. It develops and tests a conceptual relation model between trust and performance through organizational commitment and job satisfaction. It also examines contextual factors in the form of cognitive orientation of the conceptual model that has been built. The data were collected by using questionnaire-based survey method for the employees based on the criteria of having direct supervisors and directly responsible for them, and a minimum work period of one year. They were analyzed using SEM PLS. It shows that organizational commitment mediates the positive relationship between trust and job satisfaction. The positive relationship between trust and performance is mediated by organizational commitment and job satisfaction. It also shows that cognitive orientation influences the relationship between job satisfaction and performance. This study contributes to the management accounting literature, that is, a conceptual relationship model of trust to performance in the realm of empirical research